2004
DOI: 10.1002/bit.20214
|View full text |Cite
|
Sign up to set email alerts
|

Analytical monitoring of alcoholic fermentation using NIR spectroscopy

Abstract: Alcoholic fermentation under Saccharomyces cerevisiae yeasts is governed largely by glucose uptake, biomass formation, ethanol and glycerin production, and acidification. In this work, PLS calibration models were developed with a view to determining these analytical parameters from near infrared spectra and analytical data provided by the corresponding reference methods. The models were applied to a set of samples obtained from various fermentation processes. The glucose, ethanol, and biomass values predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 17 publications
0
46
1
3
Order By: Relevance
“…The optimal number of latent (factors) variables was determined by minimizing the sum of residual squared errors of prediction (PRESS), Eq. 1 (Randall, 1999;Blanco et al, 2004;Coffey and Cooley, 1999) and minimizing the root mean squared errors of prediction (Eq. 2) obtained by external validation.…”
Section: Nir Spectral Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal number of latent (factors) variables was determined by minimizing the sum of residual squared errors of prediction (PRESS), Eq. 1 (Randall, 1999;Blanco et al, 2004;Coffey and Cooley, 1999) and minimizing the root mean squared errors of prediction (Eq. 2) obtained by external validation.…”
Section: Nir Spectral Measurementsmentioning
confidence: 99%
“…Analytical spectrometry-based methods have been used to monitor ethanol fermentations (Blanco et al, 2004;Finn et al, 2006;Burratti et al, 2011), as these methods are fast and non-destructive. In addition, these methods allow simultaneous analysis of multiple parameters (Ferreira et al, 1999) without requiring sample pretreatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectroscopic Analyses -Developments and Applicationsearlier, and NIR became the standard methodology [66,67]. Later, attempts were made to use Raman spectroscopy [68].…”
Section: Monitoring Of Ethanol Production From Immobilized Yeast Usinmentioning
confidence: 99%
“…Fermentation monitoring has been investigated using NIR, mid-IR, and Raman spectroscopy because of its importance in several fields, such as food, pharmaceutical, and biological sciences and technologies. 7,[18][19][20][21][22] In our previous work, ethanol fermentation was monitored with the online NIR/mid-IR dual-region spectrometer, and principal-component analysis revealed that the detection of the end-point in the fermentation can be performed by using either transmission NIR and attenuated total reflection (ATR) mid-IR spectra based on the same chemical changes: relative changes in the concentrations of glucose and ethanol. 7 In the present study, time-dependent NIR/mid-IR spectra of the fermentation solution were acquired, and NIR bands assigned to the CH group were detected from the 2D NIR/mid-IR heterospectral correlation spectrum calculated from the obtained spectra.…”
Section: Introductionmentioning
confidence: 99%